2020
DOI: 10.1002/srin.202000434
|View full text |Cite
|
Sign up to set email alerts
|

The Flow Stress Behavior and Constitutive Model of Cr8Mo2SiV Tool Steel during Hot Deformation

Abstract: The uniaxial hot compression tests of Cr8Mo2SiV tool steel are conducted by thermomechanical simulator in a wide strain rate range of 0.005–5 s−1 and temperature range of 900–1150 °C to predict the hot deformation behavior. It is found that flow stress strongly depends on deformation temperature and strain rate under the mechanisms of dynamic softening and work hardening. Second, the Johnson–Cook model and modified Arrhenius‐type equation considering the compensation of strain are proposed for the estimation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In this section, the accuracy of different constitutive models is further quantitatively analyzed. The Pearson correlation coefficient is used in this study, which takes the form shown in Equation (24).…”
Section: Prediction Accuracy Comparison Of Different Constitutive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the accuracy of different constitutive models is further quantitatively analyzed. The Pearson correlation coefficient is used in this study, which takes the form shown in Equation (24).…”
Section: Prediction Accuracy Comparison Of Different Constitutive Modelsmentioning
confidence: 99%
“…There are numerous researches on phenomenological constitutive models for magnesium alloys, [20,21] aluminum alloys, [22,23] steels, [24][25][26][27] titanium alloys, [28][29][30] superalloy, [31][32][33] etc. Long et al [34] established an Arrhenius constitutive model to characterize the flow characteristics of ZK61 magnesium alloy.…”
mentioning
confidence: 99%
“…It describes the dynamic response of material stress to temperature, deformation rate, strain, and other process parameters under specific conditions. The Arrhenius-type models [5] are widely used in TMP, [6][7][8] owing to their simple form, easy calibration of parameters, and the ability to relatively accurately track the deformation behavior of various materials [9][10][11] throughout the entire thermomechanical process. The Arrhenius equation can be used to determine the activation energy of hot deformation [12] in relation to microstructure evolution as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, for materials whose rheological behavior is significantly affected by strain, temperature, and strain rate, since the Arrhenius-type model does not consider the influence of temperature, strain rate, and strain on model parameters, the prediction accuracy of the model for this kind of materials is not high. Through research, Li [ 10 ] and Safar [ 11 ] pointed out that the modified Arrhenius-type constitutive model considering the influence of plastic strain on model parameters could accurately predict the rheological behavior of steel under high temperature deformation. Therefore, the modified Arrhenius-type constitutive model, which can reflect the relationship between the model parameters and temperature, strain rate, and strain, is widely used to evaluate the interaction between the softening effect of dynamic recrystallization and the hardening effect of deformation under thermal deformation [ 5 , 12 ] The Johnson–Cook model is another phenomenological constitutive equation and is used to describe the rheological behavior of materials under high temperature deformation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%